PERAN SUNGAI KAMPAR DALAM SEJARAH MARITIM SEBAGAI SUMBER PEMBELAJARAN SEJARAH LOKAL - Fateha Suhaila; Fitria Amanda; Salma Wulansari; Nadia Ramona; Ahmal Ahmal (YAYASAN PADHANG MANAH SIBYAN, 2026)
The Kampar River is an important river in Riau Province, playing a significant role in Indonesia's maritime history. Since ancient times, the river has served as a transportation and trade route connecting the interior of Sumatra with the coast of the Strait of Malacca, fostering social, economic, and cultural interaction. The Kampar River is also associated with the Muara Takus Temple, a center of civilization during the Srivijaya Kingdom. This research employed a qualitative method with a historical approach. The results indicate that the Kampar River served not only as a trade and transportation route but also as a medium for the spread of culture and religion, shaping the identity of the Malay community in Riau. The Kampar River has the potential to serve as a source for maritime-based local history learning to increase historical awareness and awareness of cultural heritage